Bistable self-electro-optic operation of strained In0.1Ga0.9As/GaAs asymmetric Fabry Perot modulators - HEGARTY, JOHN (My University, 1991)
We report bistable operation of a strained-layer InGaAs/GaAs asymmetric Fabry-Perot optical modulator configured as a self-electro-optic effect device (SEED) operating in reflection mode. Bistable loops are observed from 949 to 962 nm with switching powers down to submicrowatt levels. The contrast ratio between on and off states is as large as 5:I (7 dB) and the device will hold in either state indefinitely. A 600-,um-diam device has a switching time of 20 pusf or 2.1 fJ pm - 2 switching energy. Large optical latch arrays are envisagedu sing this device.
PUBLISHED
Keywords: Physics